2014 IEEE Conference on Computational Intelligence for Financial Engineering &Amp; Economics (CIFEr) 2014
DOI: 10.1109/cifer.2014.6924082
|View full text |Cite
|
Sign up to set email alerts
|

Multi-agent pre-trade analysis acceleration in FPGA

Abstract: Background: Cognitive Muscular TherapyTM (CMT) is an integrated behavioural intervention developed for knee osteoarthritis. CMT teaches patients to reconceptualise the condition, integrates muscle biofeedback and aims to reduce muscle overactivity, both in response to pain and during daily activities. This nested qualitative study explored patient and physiotherapist perspectives and experiences of CMT.Methods: Five physiotherapists were trained to follow a well-defined protocol and then delivered CMT to at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…This is due to the introduction of new technologies in the financial market, impacting its buying and selling mechanism, which buyers need to find sellers as quickly and efficiently as possible and vice versa. For this reason, several techniques have been developed in order to identify the best trading opportunities, such as mathematical and artificial intelligence models (GERLEIN et al, 2014), as well as acceleration techniques. Another technique used to mitigate the latency is the use of general-purpose processors with specialized Network Interface Controller (NIC) (BOUTROS et al, 2017).…”
Section: Hft Machinementioning
confidence: 99%
“…This is due to the introduction of new technologies in the financial market, impacting its buying and selling mechanism, which buyers need to find sellers as quickly and efficiently as possible and vice versa. For this reason, several techniques have been developed in order to identify the best trading opportunities, such as mathematical and artificial intelligence models (GERLEIN et al, 2014), as well as acceleration techniques. Another technique used to mitigate the latency is the use of general-purpose processors with specialized Network Interface Controller (NIC) (BOUTROS et al, 2017).…”
Section: Hft Machinementioning
confidence: 99%
“…FPGAs are used for HPC in several domains, such as bioinformatics [2], linear algebra [3], stock market analysis [4] and image processing. It is shown that FPGAs can provide significant speedups in these domains [1].…”
Section: Related Workmentioning
confidence: 99%
“…In contrast to bus-based architectures, NoCs route packets of data from the source to the destination components, via a network fabric that consists of switches (routers) and interconnection links (wires). The model proposed in this paper uses the Event Driven Reactive Architecture (EDRA) introduced in [Gerlein et al 2014a] and posteriorly in [Gerlein et al 2014b], to design and implement the agents at individual level, while also implementing a hierarchical Star-NoC at social level to enable agents to communicate, cooperate and scale.…”
Section: Related Workmentioning
confidence: 99%
“…For informative events, four types of ports are defined: (a) Communication Reception Port (ComRx) -handles incoming information from inside the system; (b) External input -handles incoming information from an external source; (c) Communication Transmission Port (ComTx) -handles outgoing information inside the system; (d) External output -used to send data or information to an external destination. For a more detailed description of the EDRA we reffer the autor to [Gerlein et al 2014a] and [Gerlein et al 2014b]. …”
Section: Event Driven Reactive Architecture (Edra)mentioning
confidence: 99%
See 1 more Smart Citation